(untitled) (Orfeu, 2017)
This is a Portuguese version of what its author, Belgian musicologist Nicolas Meeùs (1944-), considered to be the founding essay for his theory of harmonic vectors. In it, Meeùs revisits the discussion of the classification of harmonic progressions, reviews the arguments of three of the 20th century’s most important music theorists, namely Hugo Riemann, Heinrich Schenker, and Arnold Schoenberg, and acknowledges the contributions of earlier theoreticians, such as Jean-Philippe Rameau, Gottfried Weber, Anton Bruckner, and Simon Sechter. The author also dialogues with his contemporary Yitzhak Sadai’s then-recent systematization, published in 1980. Finally, Meeùs applies vector analysis to works of J. S. Bach, Beethoven, and Chopin to illustrate his thesis that it is possible to reduce the syntax of harmonic progressions to two categories, the “vecteur dominant” and the “vecteur sous-dominant”. This translation of the French original, published in 1988 in Fascicules d’Analyse Musicale, received some annotations by the present authors.